Education on the Halal Certification Process of Food and Beverage Products at Village-Owned Enterprises - Kurniati, Yessy; Jafar, Nurhaedar; Hasan, Nurzakiah; Amalia, Marini; Hasan, Nurzakiah; Rosdiana, Rosdiana (Sociality: Journal of Public Health Service, 2024)
Halal certification is an important issue for business actors, because in the future every food and beverage product must have a halal certificate. Village-Owned Enterprises (Bumdes) is a business entity owned by the village and aims to develop various business products based on the existing resources in the village. Mattabulu Village, Lalabata District, Soppeng Regency, is one of the villages that has an active and accomplished Bumdes. Unfortunately, most of the food and beverage products produced by Bumdes do not have halal certificates. This service is carried out to increase the knowledge and skills of Bumdes Pada Ati members in Mattabulu Village to administer halal certificates for the food and beverage products they produce. This service is carried out using the education and training method, which begins with observing the needs of the target partners. The training was carried out effectively to increase participants' knowledge about halal certification in the good category, from 45% to 95%. As well as receiving good testimonials from participants as well as village officials and partners. It is hoped that the halal certificate will increase the competitiveness of food and beverage products produced by target partners.